Thyroid disorders and nitric oxide in cardiovascular adaptation to hypovolemia - Ogonowski, Natalia Soledad (2016)
This study aimed to investigate whether nitric oxide participates in the cardiovascular function and haemodynamic adaptation to acute haemorrhage in animals with thyroid disorders. Sprague-Dawley rats aged 2 months old treated with T3 (hyper, 20 μg/100 g body weight) or 0.02% methimazole (hypo, w/v) during 28 days were pre-treated with NG nitro-l-arginine methyl ester (L-NAME) and submitted to 20% blood loss. Heart function was evaluated by echocardiography. Measurements of arterial blood pressure, heart rate, nitric oxide synthase activity and protein levels were performed. We found that hypo decreased fractional shortening and ejection fraction and increased left ventricle internal diameter. Hyper decreased ventricle diameter and no changes in cardiac contractility. Haemorrhage elicited a hypotension of similar magnitude within 10 min. Then, this parameter was stabilized at about 30-40 min and maintained until finalized, 120 min. L-NAME rats showed that the immediate hypotension would be independent of nitric oxide. Nitric oxide synthase inhibition blunted the changes of heart rate induced by blood loss. Hyper and hypo had lower atrial enzyme activity associated with a decreased enzyme isoform in hypo. In ventricle, hyper and hypo had a higher enzyme activity, which was not correlated with changes in protein levels. Haemorrhage induced an increased heart nitric oxide production. We concluded that thyroid disorders were associated with hypertrophic remodelling which impacted differently on cardiac function and its adaptation to a hypovolemia. Hypovolemia triggered a nitric oxide synthase activation modulating the heart function to maintain haemodynamic homeostasis. This involvement depends on a specific enzyme isoform, cardiac chamber and thyroid state.